Effect and Response of Quercus ilex subsp. ballota [Desf.] Samp. Seedlings From Three Contrasting Andalusian Populations to Individual and Combined Phytophthora cinnamomi and Drought Stresses - San-Eufrasio, Bonoso; Castillejo, María Ángeles; Labella-Ortega, Mónica; Ruiz-Gómez, Francisco J.; Navarro-Cerrillo, Rafael M.; Tienda-Parrilla, Marta; Jorrín-Novo, Jesús V.; Rey, María-Dolores (Frontiers in Plant Science, 2021)
Quercus ilex L. is the dominant species in the Mediterranean forest and agrosilvopastoral ecosystem “dehesa”. Currently, this forest species is threatened by natural and anthropogenic agents, but especially by the decline syndrome, which is caused by Phytophthora cinnamomi and drought periods. Although the morphological and physiological responses of Q. ilex to combined stress (P. cinnamomi and drought) have been examined already, little is known at the molecular level. In this work, we studied the effect and response of 8-month seedlings from three contrasting Andalusian populations (Seville, Granada and Almeria) to the individual and combined of P. cinnamomi and drought stresses from morphological, physiological, biochemical and proteomics data. Whereas seedling damage (leaf chlorosis and necrosis) and mortality was greater under the combined stresses in the three populations, the effect of each individual stress was population-dependent. Resilient individuals were found in all the populations at different percentages. The decrease in leaf chlorophyll fluorescence, photosynthetic activity and stomatal conductance observed in undamaged seedlings was greater in the presence of both stresses, the three populations responding similarly to drought and P. cinnamomi. Biochemical and proteomic analyses of undamaged seedlings from the two most markedly contrasting populations (Seville and Almeria) revealed the absence of significant differences in the contents in photosynthetic pigments, amino acids and phenolics among treatments. The Seville and Almeria populations exhibited changes in protein profile in response to the different treatments, with 83 variable proteins in the former population and 223 in the latter. Variable proteins belonged to 16 different functional groups the best represented among which were protein folding, sorting and degradation, carbohydrate, amino acid, and secondary metabolism, photosynthesis, and ROS scavenging. While photosynthetic proteins were mainly down-accumulated, those of stress-responsive were up-accumulated. Although no treatment-specific response was observed in any functional group, differences in abundance were especially marked under the combined stresses. The following variable proteins are proposed as putative markers for resilience in Q. ilex: aldehyde dehydrogenase, glucose-6-phosphate isomerase, 50S ribosomal protein L5 and α-1,4-glucan-protein synthase [UDP-forming].